Indonesian Higher Education Institutions Competitiveness and Digital Transformation Initiatives - Priyanto, Panji; Suhandi, Ni Putu Mila (Jurnal Pendidikan Indonesia, 2022)
The COVID-19 pandemic was causing unexpected challenges for all education systems. Several online platforms launched by the ministry of education maximize available e-learning solutions such as virtual education resources and open classrooms, encourage the possibility of innovation and accelerated digital transformation initiatives, and further develop lecturers' digital skills and competencies. This study aims to analyze the comparative needs of the current digital environment of Indonesian higher education and conduct an in-depth study of digital learning in the Indonesian higher education environment. This study also outlines the mitigation plan, the innovative strategy adopted, and the implications and recommendations for Indonesian universities. The research method uses a discourse analysis with literature and news sources to assess the higher impact, challenges, and opportunities of education during the pandemic in Indonesia. This study finds that the COVID-19 pandemic has had a significant impact on higher education in Indonesia; Both lecturers and students in universities face many challenges in the teaching and learning process. The effect is worse in Eastern Indonesia due to poor internet connectivity for online learning. In terms of mitigating online learning, the impact is still unknown. The limitation in this study states that the literature and news studies are not comprehensive because the current pandemic crisis has not ended. This study can represent an illustration of the limitations of a more empirical study to be conducted on how the current crisis affects the learning process of Indonesian universities.